Protection of renal damage by HMG-CoA inhibitors: A comparative study between atorvastatin and rosuvastatin - Jabarpour, Maryam (Iran J Basic Med Sci, 2020)
OBJECTIVE(S): Hypercholesterolemia is a common metabolic disorder in developing and developed countries and is associated with the increased rates of chronic kidney disease (CKD). Statin therapy could reduce cholesterol synthesis as well as progression of CKD. Diversity between statins causes variety in pharmacokinetics and pharmacodynamics and also their pleiotropic effects. In the present investigation we aimed to evaluate the protective potentials of both atorvastatin (Ator) (as lipid-soluble statin) and rosuvastatin (Ros) (as water-soluble statin) against renal histopathological damages in the high cholesterol diet induced hypercholesterolemic rats (HCDIHR). MATERIALS AND METHODS: Serum lipid profile, oxidized low density lipoprotein (OX-LDL), malondialdehyde (MDA), urea and creatinine levels, as well as renal histopathology were evaluated. RESULTS: While Ros acted better than Ator to reduce serum low density lipoprotein cholesterol (LDL-C) (P<0.01), atherogenic index (AI) (P<0.01), MDA (P<0.01), and OX-LDL (P<0.01); no significant differences were noted in their cholesterol (P=0.72), triglyceride (TG) (P=0.79), and very low density lipoprotein cholesterol lowering (VLDL-C) (P=0.79) and high density lipoprotein cholesterol elevating effects (HDL-C) (P=0.72). Ator was more effective to reduce renal histopathologic indices compared to Ros, including accumulation of lipid droplet, glomerular foam cells, mesangial cell proliferation, renal hemorrhage, and tubulointerstitial damages in the kidneys of diet induced hypercholesterolemic rats. CONCLUSION: The findings underline that the lipophilic Ator may performs better than Ros in attenuating renal damages in HCDIHR.